Base Metal Catalyzed Isocyanide Insertions. (4th October 2019) - Collet, Jurriën W.; Roose, Thomas R.; Ruijter, Eelco; Maes, Bert U. W.; Orru, Romano V. A.
Abstract: Isocyanides are diverse C1 building blocks considering their potential to react with nucleophiles, electrophiles, and radicals. Therefore, perhaps not surprisingly, isocyanides are highly valuable as inputs for multicomponent reactions (MCRs) and other one‐pot cascade processes. In the field of organometallic chemistry, isocyanides typically serve as ligands for transition metals. The coordination of isocyanides to metal centers alters the electronic distribution of the isocyano moiety, and reaction pathways can therefore be accessed that are not possible in the absence of the metal. The tunable reactivity of the isocyanide functional group by transition metals has evolved into numerous useful applications. Especially palladium‐catalyzed isocyanide insertion processes have emerged as powerful reactions in the past decade. However, reports on the use of earth‐abundant and cheap base metals in these types of transformations are scarce and have received far less attention. In this Minireview, we focus on these emerging base metal catalyzed reactions and highlight their potential in synthetic organic chemistry. Although mechanistic studies are still scarce, we discuss distinct proposed catalytic cycles and categorize the literature according to 1) the (hetero)atom bound to and 2) the type of bonding with the transition metal in which the (formal) insertion occurs. Abstract : Basismetall‐katalysierte Reaktionen mit Isocyanid‐Insertion haben sich jüngst zu vielversprechenden Kreuzkupplungen entwickelt. Auch wenn mechanistische Studien bislang kaum beschrieben wurden, werden in diesem Kurzaufsatz vorgeschlagene Katalysezyklen besprochen und die diskutierten Beispiele entsprechend kategorisiert. Dies sollte die Entwicklung neuer Reaktionen für die effiziente Synthese wertvoller Verbindungen erleichtern.